Evaluation Strength of Materials of the Compressor Wheel and Engine Power in the Turbocharger - Danh, Tran Huu; Ky, Le Hong; Anh, Pham Hoang; Tam, Dang Thanh; Hiep, Nguyen Hoang (Engineering, Technology & Applied Science Research, 2024)
This paper presents the research results on the strength of materials and power of the Toyota 3C engine when changing the structure and number of blades of the compressor wheel in the turbocharger. 3D models of different compressor wheels were created using reverse engineering and then simulated in the ANSYS environment with turbine shaft rotation speeds of 10,000, 15,000, and 20,000 rpm, respectively, to examine the strength of the compression wheel materials. To evaluate engine power, compressor wheels were machined on a 5-axis CNC milling machine. The MP 100S specialized test bed was used to perform experiments and compare engine power when using the original and alternative compressor wheels of the CT9 turbocharger. The compressor wheels were made of aluminum alloy, with a structure and number of blades selected to ensure durability when working. The CT9 turbocharger has a four-pair blade compressor wheel that consistently delivers higher engine power than in other cases.